Respuesta :
We first simplify the parentheses to get:
4x-2+3x+5
Now, combining like terms, we have 7x+3 as the most simplified expression.
4x-2+3x+5
Now, combining like terms, we have 7x+3 as the most simplified expression.
simplify step-by-step.
4x−(2−3x)+5
=4x+−2+3x+5
Combine Like Terms:
=4x+−2+3x+5
=(4x+3x)+(−2+5)
[tex]\huge{\boxed{\boxed{\boxed{\boxed{\boxed{7x + 3}}}}}}[/tex]
4x−(2−3x)+5
=4x+−2+3x+5
Combine Like Terms:
=4x+−2+3x+5
=(4x+3x)+(−2+5)
[tex]\huge{\boxed{\boxed{\boxed{\boxed{\boxed{7x + 3}}}}}}[/tex]